53PZNF518B as a transcriptional factor involved in colorectal cancer progression through the epithelial to mesenchymal transition. (7th November 2019) - Valiente, F G; Tarazona, N; Gambardella, V; Riffo-Campos, Á; Papaccio, F; Cabeza-Segura, M; López-Rodas, G; Cervantes, A; Franco, L; Castillo, J
Abstract: Background: Colorectal cancer (CRC) represents a relevant public health problem. The identification of new markers involved in the mechanisms of invasiveness represents a priority in order to better understand cancer development and generate new therapeutic targets. Recently, our group demonstrated overexpression of ZNF518B gene, which encodes an unknown zinc finger transcription factor, in CRC. A transcriptome-wide gene expression profile revealed its implication in different biological processes related to the progression of CRC, especially in the epithelial to mesenchymal transition (EMT). Methods: To study the biological processes regulated by ZNF518B, we performed a ClariomS Array (Affimetrix) by silencing this gene with a specific siRNA in DLD1 and HCT116 CRC cell lines. All data were analysed using the TAC (Transcriptomic Analysis Console TM ) software. The array validation was performed by RT-qPCR. To explore the in vitro mechanisms related to EMT, an overexpression of ZNF518B was performed in RKO, cell line that does not express the gene. Invasion and migration assays were done using transwells and we also test adhesion capacity to type I collagen plates. Results: The analysis of ClariomS showed, after the silencing of the transcription factor ZNF518B, an alteration of 64 genes commonly modified in the DLD1 and HCT116 cell lines. These differentially expressed genes are involved in different biological processes involved in cellular focal adhesion, in the EMT process and in cell cycle. On the other hand, some proliferation pathways are also altered like MAPK, RAS, WNT and VEGFR2 signalling pathways. Through in vitro analysis, we showed that the increased expression of ZNF518B enhanced cell migration, invasion and adhesion to type I collagen. These results in vitro support the altered gene expression profile after ZNF518B silencing observed in the ClariomS array, suggesting that this gene has an important role in the progression of CRC throughout EMT. Conclusions: The transcription factor ZNF518B could be involved in the progression of tumorigenesis by inducing EMT in CRC.The transcription factor ZNF518B could be involved in the progression of tumorigenesis by inducing EMT in CRC. Legal entity responsible for the study: INCLIVA, Biomedical Research Institute. Funding: Instituto de Salud Carlos III, Rio Hortega Contract, ESMO Translational Research Fellowship Programme. Disclosure: A. Cervantes: Advisory / Consultancy, Speaker Bureau / Expert testimony, Research grant / Funding (institution): Merck Serono; Advisory / Consultancy, Speaker Bureau / Expert testimony, Research grant / Funding (institution): Roche; Advisory / Consultancy, Research grant / Funding (institution): Beigene; Advisory / Consultancy, Research grant / Funding (institution): Bayer; Advisory / Consultancy, Speaker Bureau / Expert testimony, Research grant / Funding (institution): Servier; Advisory / Consultancy, Research grant / Funding (institution): Lilly; Advisory / Consultancy, Research grant / Funding (institution): Novartis; Advisory / Consultancy, Research grant / Funding (institution): Takeda; Advisory / Consultancy, Research grant / Funding (institution): Astellas; Advisory / Consultancy: Pierre Fabre; Research grant / Funding (self): Genentech; Research grant / Funding (institution): Fibrogene; Research grant / Funding (institution): Amcure; Research grant / Funding (institution): Sierra Oncology; Research grant / Funding (institution): AstraZeneca; Research grant / Funding (institution): MedImmune; Research grant / Funding (institution): BMS; Research grant / Funding (institution): MSD; Speaker Bureau / Expert testimony: Amgen; Speaker Bureau / Expert testimony: Fundation Medicine. All other authors have declared no conflicts of interest.